2013
DOI: 10.1111/aji.12150
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Administration of Peripheral Blood Mononuclear Cells (PBMCs) Improves Endometrial Receptivity in Mice with Embryonic Implantation Dysfunction

Abstract: Intrauterine administration of mouse PBMCs derived from unpregnant mice prior to embryo implant has a good influence on endometrial receptivity and embryonic implantation in EID mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
4
50
0
1
Order By: Relevance
“…Our study showed that LIF and IL-1β expressions are significantly increased in human PBMC incubated with rhCG for 24 h compared with that in PBMC incubated without rhCG, a finding that was similar to those in previous studies in mice and bovine [12, 20]. In addition, Ideta et al [11] cultured bovine PBMC with hCG for 24 h and confirmed elevated production of cytokines such as IL-1α, IL-1β, and IL-8.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed that LIF and IL-1β expressions are significantly increased in human PBMC incubated with rhCG for 24 h compared with that in PBMC incubated without rhCG, a finding that was similar to those in previous studies in mice and bovine [12, 20]. In addition, Ideta et al [11] cultured bovine PBMC with hCG for 24 h and confirmed elevated production of cytokines such as IL-1α, IL-1β, and IL-8.…”
Section: Discussionsupporting
confidence: 91%
“…Later, Okitsu et al [41] found that intrauterine administration of freshly isolated PBMC effectively improved embryo implantation in patients receiving frozen/thawed embryo transfer after three or more repeated in vitro fertilization failures. We previously proposed that the intrauterine administration of hCG-activated murine PBMC could promote embryonic implantation by regulating endometrial receptivity, providing a possible mechanism of this new immunotherapy [12]. However, the effects of hCG on PBMC function derived from non-pregnant women in vitro and the physiological effect of activated PBMC on trophoblasts at the early implantation site remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage-derived LIF facilitates development of implantation-receptive endometrium by modulating the surface glycan structure of epithelial cells [59] as well as regulating the expression of fucosyltransferase enzyme in the uterine epithelia which is involved in the synthesis of embryo adhesive fucosylated glycoconjugates during the period of inflammatory response towards insemination [60]. A recent study reported that intrauterine administration of peripheral blood mononuclear cells (PBMCs) in mice helped to improve endometrial receptivity as evidence from a high pregnancy rate associated with increased endometrial LIF and vascular endothelial growth factor (VEGF) expressions [61]. PBMCs were found to produce cytokines and angiogenic factors necessary for implantation [56].…”
Section: Lif Role In Leukocyte Recruitment During Implantationmentioning
confidence: 99%
“…Bmal1, Per1, and Per2 knockout mice have all been shown to have deficiencies in embryonic implantation and pregnancy maintenance [21]. Priyanka et al found that menstrual cycle alters immune reactivity, enzyme activities and intracellular signaling pathways in PBMCs of healthy women [22] and PBMCs have been demonstrated to be correlated with embryo implantation [23]. It is possible that these alternations are partly due to the changes of the clock gene expression in PBMCs.…”
Section: Commentsmentioning
confidence: 99%